Regime-Dependent Environmental Tax Multipliers Evidence from 75 Countries - Schoder, Christian (The World Bank, 2021)
The paper uses a new country-level, panel data set to study the effect of public sector wages on corruption. The results show that wage inequality in the public sector is an important determinant of the effectiveness of anti-corruption policies. Increasing the wages of public officials could help reduce corruption in countries with low public sector wage inequality. In countries where public sector wages are highly unequal, however, raising the wages of government employees could increase corruption. These results are robust to a wide range of empirical model specifications, estimation methods, and distributional assumptions. The relation persists when controlling for latent omitted variables, using the share of contracts in the private sector as an instrument for the public-private wage differential. Combining increases in public sector wages with policies affecting the wage distribution could help policy makers design cost-effective programs to reduce corruption in their countries